Pengaruh Integrasi Model Pembelajaran Think-Pair-Share dengan Make A Match terhadap Aktivitas dan Hasil Belajar Siswa - Dayu Janua Lestari; Taufik Samsuri; Siti Rabiatul Adawiyah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2017)
This study aims to determine the effect of the integration of think pair share learning models with make a match toward the students’ activities and cognitive learning outcomes of class X MA Raudlatusshibyan NW Belencong. This study was a quasi-experimental research with posttest-only control group design. The population in this study were 55 students of class X which were divided into 2 classes. The sample in this study is class X.1 and class X.2 using saturated sampling techniques. Data collection is done by using instruments in the form of observation sheets and student learning outcomes tests. Based on the data analysis, the results of the observation of the learning activities of the experimental class students with an average value of 10.70 are in the active category, while the average value of the control class is 4.96 in the moderately active category. Based on the results of the data analysis it can be seen that the student learning activities of the experimental class are categorized as active while in the control class they are quite active. The cognitive learning outcomes of the experimental and control class students after being analyzed using the t-test were obtained for the tcount of (1.73) the value was smaller than the value of ttable (2,000). Based on these results it can be seen that there is no effect of the integration of the think pair share learning model with make a match toward the cognitive learning outcomes of class X MA Raudlatusshibyan NW Belencong.